Real-World Effectiveness and Safety of Upadacitinib in Tumor Necrosis FactorInhibitor Refractory Axial Spondyloarthritis: 52-Week Outcomes from a Single-Center Cohort - Bakay, Umut; İzci Duran, Tuğba (Archives of Rheumatology, 2025)
Background/Aims: Patients with axial spondyloarthritis (axSpA) who fail tumor necrosis factor inhibitors (TNFi) represent a treatment-refractory subgroup with limited options. Real-world evidence (RWE) on the effectiveness and safety of selective Janus kinase 1 (JAK1) inhibition in this setting remains scarce. This study aimed to evaluate the 52-week real-world effectiveness, persistence, and safety of upadacitinib in TNFi-refractory axSpA patients. Materials and Methods: In this retrospective, single-center study, 45 Turkish axSpA patients with prior TNFi failure received upadacitinib 15 mg daily and were assessed at weeks 12, 24, and 52. Effectiveness outcomes included Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI), Health Assessment Questionnaire (HAQ), Visual Analog Scale for pain, and Assessment of SpondyloArthritis International Society (ASAS) 20/40/70 responses analyzed with non-responder imputation (NRI). Treatment persistence was evaluated by Kaplan–Meier analysis, predictors of discontinuation by Cox regression, and safety outcomes as incidence per 100 patient-years (PY). Results: Mean age was 48.1 years; 53.3% were male; 68.9% human leukocyte antigen B27 positive. At week 52, BASDAI and ASDAS decreased significantly (both P < .001), with parallel improvements in BASFI, BASMI, HAQ, and pain. The ASAS20/40/70 responses were achieved by 75.6%, 60.0%, and 26.7% of patients (NRI). Drug retention was 75.6% at 1 year; discontinuations occurred due to adverse events (AEs) (4.4%), treatment failure (11.1%), patient decision (6.7%), and pregnancy (2.2%). Prior interleukin-17 inhibitor (IL-17i) exposure (HR 3.88) and multiple TNFi use (HR 3.02) predicted shorter drug survival. Across 38.3 PY, no serious infections, malignancies, or thromboembolic events were observed; AEs were infrequent and manageable. Conclusion: Upadacitinib provided sustained improvements in disease activity, function, and patient-reported outcomes in TNFi-refractory axSpA, with favorable persistence and safety. Despite limitations of the retrospective, single-center design and modest sample size, these findings complement pivotal trials and global real-world data and represent the first RWE of upadacitinib use in Türkiye, supporting JAK1 inhibition as a therapeutic option in difficult-to-treat populations. Cite this article as: Bakay U, Duran Tİ. Real-world effectiveness and safety of upadacitinib in tumor necrosis factor-inhibitor refractory axial spondyloarthritis: 52-week outcomes from a single-center cohort. Arch Rheumatol. 2025;40(4):465-473.